2010
DOI: 10.4103/1658-354x.65122
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of ketamine or nitroglycerin as an adjuvant to lidocaine improve the quality of intravenous regional anesthesia?

Abstract: Aims:To compare and evaluate the effect of adding ketamine or nitroglycerin (NTG) as adjuncts to lidocaine for intravenous regional anesthesia (IVRA) on intraoperative and postoperative analgesia, sensorial and motor block onset times, and tourniquet pain.Settings and Design:A prospective, randomized, double-blind study was carried out.Materials and Methods:Seventy-five patients undergoing hand surgery were divided into three groups as follows: control group receiving lidocaine 2%, LK group receiving lidocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…A conjoint administration of lidocaine with ketamine shortens the onset of anesthesia in mice and improves the anesthetic efficacy without prolonging the recovery time. 30,31 Besides, the addition of ketamine to epidural lidocaine or bupivacaine as an additive anesthetic has been identified to increase the duration of regional anesthesia and postoperative analgesia, and peri-incisional use of 0.3%-0.5% ketamine combined with local anesthetic in surgical wounds could enhance analgesia. 32 Pretreatment with a combination of intravenous lidocaine 40 mg and ketamine 25 mg is a more effective anesthetic than lidocaine 40 mg or ketamine 25 mg alone in preventing subsequent pain.…”
Section: Discussionmentioning
confidence: 99%
“…A conjoint administration of lidocaine with ketamine shortens the onset of anesthesia in mice and improves the anesthetic efficacy without prolonging the recovery time. 30,31 Besides, the addition of ketamine to epidural lidocaine or bupivacaine as an additive anesthetic has been identified to increase the duration of regional anesthesia and postoperative analgesia, and peri-incisional use of 0.3%-0.5% ketamine combined with local anesthetic in surgical wounds could enhance analgesia. 32 Pretreatment with a combination of intravenous lidocaine 40 mg and ketamine 25 mg is a more effective anesthetic than lidocaine 40 mg or ketamine 25 mg alone in preventing subsequent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine also has local anesthetic qualities, which have been studied as a sole agent for IVRA. [7] In addition to spinal cord NMDA receptors, NMDA receptors have also been identified on peripheral unmyelinated sensory axons. This can explain why ketamine as an NMDA receptor antagonist was able to attenuate the tourniquet pain.…”
Section: Discussionmentioning
confidence: 99%
“…Elmetwaly et al [6] studied the effect of adding ketamine or nitroglycerin to lidocaine for Bier's block on seventy-five patients undergoing hand surgery and found that, in the control group, the starting four hours postoperatively, the VAS scores were higher compared with the other study groups. Also, Cakmak et al [5] noted and agreed these results by approving that, in Group C, the starting four hours postoperatively, the VAS scores were higher in comparison to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several adjuncts have been used including narcotics, nonsteroidal anti-inflammatory drugs (NSAIDs), muscle relaxants, α 2 agonists, and neostigmine [6]. …”
Section: Introductionmentioning
confidence: 99%